PERANCANGAN MEDIA PROMOSI PRODUKSI “KOPIAH JANGANG” MENGGUNAKAN TEKNIK VIDEOGRAFI DAN SINEMATOGRAFI - Romadoni, Jiki; Mailansa, Eko; Hakim, Beny Rahman; Rizky, Muhammad; Makie, Haji Ahmad (Jurnal Teknoinfo, 2024)
This research aims to improve promotion and information about handicraft products "Kopiah Jangang" from Beringin B Village, Tapin Regency. Currently, the production site is constrained in the sales section which only delivers from shop to shop and also the production house is constrained because it cannot use smartphones in marketing Jangang Kopiah, and there is no promotional video that can help market the product more widely. The method used is the Multimedia Development Life Cycle (MDLC). The result is a promotional video with a duration of 4:38 minutes that pays attention to each scene and the meaning that is inserted to help "Kopiah Jangang" craftsmen and the Tapin Regency Tourism Office in promoting this product. In conclusion, this promotional video successfully uses Videography and Cinematography techniques well.